Characterization of glutenin genes in cereals and their contribution to the gluten properties - Jouve N.; Soler C.; Rubio P.; Bernardo A.; Cuadrado A.; Peña E.; De Bustos A. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
It is analyzed the primary structure of some of the high molecular weight (HMW) glutenin genes and their degree of conservation in the genera Triticum, Secale and Aegilops. The primary structure presented information on the allelic composition and the quantities of the endosperm protein fractions (HMW, LMW and gliadins) in the doughs of different common wheat cultivars and lines in process of selection. Dough W is correlated with the quantity of HMW subunits present in the gluten and in particular with the quantity of type x HMW subunits. The gliadins and the LMW subunits appear to act as a 'solvent' which modifies the rheological properties of the dough by interfering with the polymerization of the HMW subunits, or by altering the relative amounts of the different types of subunits available. The contribution of each type of subunit in the organization of the intermolecular links, the formation of the multiproteic aggregates, and the properties of the gluten, is discussed.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)